IMPROVEMENT OF LEARNING RESULTS THROUGH THE WEEKLY PROJECT OF PROBLEM SCHEME WITH THE TEACHING AT THE RIGHT LEVEL APPROACH - Prasetiyo, M. Mahmudi; El Walida, Sikky (JME (Journal of Mathematics Education), 2025)
The problems that occur in learning outcomes are generally influenced by learning activities that are less interactive and less interesting so as to reduce student motivation and enthusiasm, which is caused by the learning methods and styles used in the classroom. Based on observations at SMAN 8 Malang, it is known that the implementation of mathematics learning is still one-way and students are only involved in doing assignments. This has an impact on the results of the assessment carried out by the teacher in learning mathematics. To improve student learning outcomes, effective and relevant learning methods are needed in accordance with the lesson plans that have been prepared. The approach and learning model that aims to provide solutions to overcome the challenges of improving learning outcomes is the Weekly Project of Problems (W-PoP) Scheme with the TARL Approach. The research method used is Classroom Action Research with data collection techniques consisting of initial assessment, observation, written tests, interviews, and questionnaires.  Through this research, an increase in the percentage of student learning completeness was obtained in the summative assessment in cycle 2 which reached 79%, an increase of 32% compared to the summative assessment in cycle 1 and an increase of 38% from the pre-cycle. The average score of all students also increased significantly in each cycle. Thus, the application of the Weekly Project of Problems (W-PoP) with the TARL Approach can provide equal opportunities for students to receive learning materials and have equality in getting treatment in learning to gain understanding abilities to improve student learning outcomes.